Draft Annual Plan 1972-73 Laccadive, Amindivi , and Minicoy Islands - Planning Commission (Planning Commission, 1973)
The coral islands of the Aram a Sea known as. Laccadive, Minicoy and Amindivi Inlands are twenty in number, including the bird island of Pitti. Out of tense, ten are inhabited and nine are uninhabited but are cultivated. Pitti is neither inhabited nor cultivated. These Islands lay about-200 to 400. Kilometers. off the Kerala coast between 8 and 12 -13 north Latitude & between 70 and 749 east longitude. The entire, inhabitants of that islands are Muslins and are classified as Scheduled Tribe’s. Lack of dependable and regular means of conveyance to the mainland was a major problem faced by these islands. The islands remained cut off during the monsoon months till the introduction of the pew' all weather ship M.V. Amindivi' in April 1970. Social and Economic development of the people is the basic approach of the Fourth Plan. Agriculture, Fisheries, Cooperation and Education have been given importance. Development of Cottage Industries is also envisaged.
Draft Annual Plan 1972-73
Government of India Planning Commission
Keywords: The financial Outlook; Sectoral Programmes; Programme For Backward Areas Communities; Administrative Policy and Institutional Frame Work; Animal Husbandry; Fisheries; Co-operation; Community Development; Power; Industries; General Education; Pre-Primary Education